"Intelligent" Technical Guidelines for Chongqing East Railway Station Building and Supporting Hub Area. (19th April 2021) - Shi, Jingyuan; Li, Qiuna
Abstract : In this paper, by drawing on the advanced experience and norms at home and abroad, the compilation and research of "intelligent technical guidelines" for Chongqing east railway station and its supporting hub area are completed. It includes "digital technology, intelligent construction, " "accurate and flexible, intelligent service, " and "panoramic management and control, intelligent operation, and maintenance, " and has formed the whole life cycle technical framework of "intelligent construction, intelligent service, intelligent management, and operation and maintenance."